Clinical characteristics and outcomes of lung cancer patients with combined pulmonary fibrosis and emphysema: a systematic review and meta-analysis of 13 studies - Li, Chuan; Wu, Wenwen; Chen, Nan; Song, Huizi; Lu, Tianjian; Yang, Zhenyu; Wang, Zihuai; Zhou, Jian; Liu, Lunxu (Journal of Thoracic Disease; Vol 9, No 12 (December 29, 2017): Journal of Thoracic Disease, 2017)
Background: The characteristic and outcomes of lung cancer patients with combined pulmonary fibrosis and emphysema (CPFE) have long been assessed, but results were controversial. Therefore, we performed a meta-analysis to assess the clinical features and prognosis of lung cancer patients with CPFE. Methods: The databases PubMed, Embase, and Web of Science (updated to October 1, 2017) were searched for eligible studies. Pooled odds ratios (ORs), weighted mean differences (WMD) or hazard ratios (HRs) with 95% confidence intervals (95% CIs) were used to evaluate the clinicopathological characteristics, the short-term outcome after operation and long-term survival of lung cancer patients with CPFE compared with lung cancer patients without CPFE (fibrosis, emphysema, and normal). Results: Thirty original studies with 8,050 patients were included in this meta-analysis. The pooled results indicated that lung cancer patients with CPFE were associated with higher age (MD =3.39; 95% CI: 2.12–4.67, P